Features of the use of big data in the financial sector - F. O. Chernenkov (Вестник университета)
The purpose of  the article is   to theoretically comprehend the essence of   big data, identify the advantages and risks of   its use by   financial organisations. The article presents the results of   systematisation of   knowledge about the nature and features of  the big data. It  has been revealed that the technology makes it   possible to  do better analytical research, create models for forecasting economic trends and market changes, study market dynamics, analyse medical data to  improve diagnosis and choice of   treatment methods, predict failure or  breakdown of   equipment in  production by   assessing data from sensors, develop social and economic programmes at   the state level, identify fraud and corruption in   the financial sector, etc. The relevance of   the rapid development of  the big data technology and the expediency of   its use in   this sphere is   substantiated. As a   result of   the analysis of   scientific literature, the author’s definition of   the technology in  the financial sector is   presented. Its novelty lies in  considering the features and advantages of   applying the big data by   financial organisations. The study of   the modern practice of   their usage in   these institutions has revealed the main strengths and disadvantages of   the technology in   question.